Understanding the Dynamics of Internship Experience: The Case of the Hashemite University Preservice Primary Science Teachers - Qablan, Ahmad (Jordan Journal of Educational Sciences, 2006)
This study attempted to understand the dynamics of internship experience at the Hashemite University in Jordan. A qualitative research approach was used to answer the research questions. Data collected in this study were derived from participants’ interviews, classroom observations, and teaching artifacts. Among twelve preservice science teachers, three were chosen to collect the needed data. Results of the study provided evidence that the internship period is a stressful experience for intern students. Lack of help and support from school principals and cooperative teachers were among the major difficulties that faced participants. The study suggests that internship experience is a critical stage for new teachers and should be made easy to them with the help and support of all members involved in the internship program. This research also provides strategies to help intern science students employ inquiry-based teaching strategies in their teaching.